The relationships between Fatimah, the daughter of prophet Mohammed peace be upon him, and Abu Baker and Omar, may God be pleased with them all - Alhabardi, Hadi Qaed (Journal of Islamic Sciences, 2023)
Those events that occurred in the era of the advent of Islam had great importance and consequently strong influence on what followed them in terms of intellectual transformations and the emergence of different doctrines. Among those events was the relationship of Fatima, the daughter of prophet Mohammed peace be upon him, with Abu Baker and Omar, may God be pleased with them all. Using the historical - critical method, the scholar tries to question the historical suspicions which occurred repeatedly in Sunni and Shiite recourses concerning the bad relationship between them. Among the most important suspicions are the relationships between their families before and during Hijra (migration), the proposals of Abu baker and Omar to Fatimah, their roles in her marriage to Ali, her refusal to pledge allegiance to Abu Baker, the suspicious claims of harming her, the inheritance of her father’s legacy, her anger, her abandoning Abu Bakr, the type of the relationships they have together and finally the reasons for her burial at night after her death. The research concluded that their relationship wasn’t hostile but rather was characterized by mutual respect, friendliness and appreciation.